2007
DOI: 10.2109/jcersj.115.160
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Porous Titania Using Anisotropic Particles

Abstract: Porous materials were prepared by stacking needle-like titania particles. The uniform, needle-like titania particles were synthesized by hydrothermal treatment of titanium hydroxide gel containing ethylenediamine. A seeding technique controlled the particle size of them. The obtained particles were dispersed in aqueous solutions with various pH values and vacuum-filtered to form bulk materials. Porous materials with uniform microstructure were obtained when the pH of the suspension was adjusted to the value su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
(3 reference statements)
0
10
0
Order By: Relevance
“…The set of nine non-linear simultaneous equations (5)(6)(7)(8)(9)(10)(11)(12)14) was solved numerically. The total number density of adsorption sites is Γ 0 = 5 nm −2 as a literature-based value [18].…”
Section: Iii2 Model Of Charging Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…The set of nine non-linear simultaneous equations (5)(6)(7)(8)(9)(10)(11)(12)14) was solved numerically. The total number density of adsorption sites is Γ 0 = 5 nm −2 as a literature-based value [18].…”
Section: Iii2 Model Of Charging Behaviormentioning
confidence: 99%
“…Recently, shape controlled needle-like anatase-type titania nanoparticles are well-studied, because of their characteristic chemical and physical properties [9,10]. Nevertheless, the effect of the shape controller on the surface charging and IEP of needle-like TiO 2 nanoparticles has not yet been systematically studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35),36) Consequently, if morphologically uniform anisotropic boehmite particles are prepared and arrayed in an ideal form, then porous alumina with a uniform microstructure and high porosity can be obtained. 37), 38) The authors have reported a simple fabrication procedure of porous alumina using needle-like particles. 38) As starting particles for porous alumina fabrication, anisotropic boehmite particles were prepared using the "gelsol" method.…”
Section: Introductionmentioning
confidence: 99%
“…6),7) The authors reported a fabrication technique of porous ceramics using uniform, anisotropic titania particles. 6) Fabrication of porous titania with a uniform pore structure was achieved simply by stacking the particles using a vacuum filtration of the suspension. We designate the thusprepared porous materials as porous compacts.…”
mentioning
confidence: 99%